Online Teaching during COVID-19 in Bangladesh: Challenges Faced by the EL Teachers - Rouf, Md Abdur; Rashid, Harun (Journal of NELTA, 2021)
The study explored the challenges faced by secondary and higher secondary English language (EL) teachers in Bangladesh while teaching their learners online during the COVID-19 pandemic. Like teachers in most countries across the world, Bangladeshi EL teachers had to abruptly switch to online mode of teaching from in-person classes without much preparation. Following the constructivist research paradigm and a qualitative multiple case study approach, four secondary and four higher secondary EL teachers were interviewed to gather in-depth data on the challenges they encountered. The findings showed that the main challenges for the teachers included: unavailability of devices, falling interest, poor attendance of learners, less interaction in classes, lack of technological skills and training, financial hardship, unstable internet connections, almost no practice of language skills, lack of online testing schemes, negative mental and physical impacts, and the overall perceived ineﬃcacy of online EL classes. The paper also discusses the implications of the main findings and proposes some recommendations for the teachers and other stakeholders concerned.